Institution of the electoral commissioner and electoral officials after the amendment of the electoral code - Frydrych-Depka, Anna (Studia Iuridica Toruniensia, 2019)
The article is devoted to two institutions of electoral law, which role is significant in the conduct of local elections. They are the electoral commissioner and electoral officials. A recent amendment to the Electoral Code made by the Act of 11 January 2018 on amending certain acts to increase the participation of citizens in the process of selecting, operating and controlling certain public bodies was intended to prevent the repetition of the organizational clutter that took place in the 2014 local elections. The purpose of the text is to verify whether modifications made to the institution of the election commissioner and the establishment of the Corps of Election Officers can pursue this objective.